PENTINGNYA PENDIDIKAN KARAKTER BANGSA GUNA MEREVITALISASI KETAHANAN BANGSA - Yuliana, E. Dewi (Buletin Udayana Mengabdi, 2012)
Character education to revitalize the nation’s resilience of nations must be done immediately, because many multi-dimensional crisis are faced by the Indonesian people. Multi-dimensional crisis are attributed by the changing dynamics of world order with the strengthening of globalization. They are also caused by modernization, industrialization, regional autonomy , environmental, moral and intellectual degradations, the potential for conflict between groups (race, ethnicity, religion), as well as by infrastructure Nationality, statehood, and crisis-prone society. Character education aims to optimize the cargo-load of good character and positive (traits, attitudes, and behavior of nobility that became a strong grip and the authorized individual and the nation’s future development. Education is considered very important character both at various levels and occasions, also begins at home, school, up to life in society. Planting the values and spirit implied in Pancasila and Unity in diversity can be developed into a reality in strengthening the national identity. It can be an inspiration to the strengthening of national character education. Thus, the future progress of the nation, especially in matters of national character education should be borne jointly by both countries, communities, and all components of the nation Indonesia.